The Temporal Retinal Nerve Fiber Layer Thickness Is the Most Important Optical Coherence Tomography Estimate in Multiple Sclerosis - Birkeldh, Ulrika; Manouchehrinia, Ali; Hietala, Max Albert; Hillert, Jan; Olsson, Tomas; Piehl, Fredrik; Kockum, Ingrid Skelton; Brundin, Lou; Zahavi, Ori; Wahlberg-Ramsay, Marika; Brautaset, Rune; Nilsson, Maria (Frontiers in Neurology, 2017)
Background: Reduced peripapillary retinal nerve fiber layer (pRNFL) and combined ganglion cell and inner plexiform layer (GCIP) thicknesses as measured by optical coherence tomography (OCT) have been observed in MS patients. The purpose was to determine the most associative OCT measure to level of cognitive and physical disability in MS. Methods: Data was collected from 546 MS patients and 175 healthy controls (HCs). We compared the average peripapillary RNFL (pRNFL), temporal pRNFL (tRNFL), overall inner ganglion cell/inner plexiform layer (GCIP) and the overall ganglion cell complex (GCC) including macular RNFL and GCIP thicknesses measurements in differentiating MS subtypes from HCs. The association between OCT measures, EDSS and SDMT were assessed using Generalized Estimating Equations models. Results: Both peripapillary and macular OCT measurements could differentiate all MS subtypes from HCs. The SDMT score was significantly associated with reduced thickness of all OCT measures, mostly in average pRNFL (0.14 µm, P = 0.001) and tRNFL (0.17 µm, P < 0.001). The EDSS score was significantly associated with reduced inner retinal layer thickness. The largest reduction was seen in tRNFL (-1.52 µm, P < 0.001) and inner GCC (-1.78 µm, P < 0.001). Conclusion: The tRNFL is highly sensitive and associated with level of both cognitive and physical disability.